PERBEDAAN KUALITAS TIDUR YANG BURUK PADA REMAJA YANG KECANDUAN DAN TIDAK KECANDUAN SMARTPHONE - Irwina Angelia Silvanasari; Hella Meldy Tursina (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2021)
Introduction: An adolescent aggregate is an age group with a high rate of smartphone addiction. Poor sleep quality in adolescents is one of the negative effects resulting from smartphone addiction Objective: To analyse poor sleep quality differences among adolescents with smartphone addiction compared to those without Methods: Analytical observational design with a cross-sectional approach was used in this study, involving 165 secondary school students as the participants. Study variables include smartphone addiction and poor sleep quality. The instruments used for data collection are the Pittsburgh Sleep Quality Index (PSQI) questionnaire and the Smartphone Addiction Scale: Short Version (SAS-SV). The statistical analysis performed was the Mann Whitney test. Results: The statistical test results obtained a p-value < alpha (0,000 < 0,05), which means at a 95% confidence level, there was a difference in the poor sleep quality score between adolescents with smartphone addiction compared to those without. Adolescents with smartphone addiction have higher poor sleep quality scores compared to adolescents without smartphone addiction. Conclusion: Adolescents should be able to limit the use of the smartphone according to their needs and minimise smartphone use before going to bed at night.